Agency Theory and Antifragility: Formation of Filipino Teachers - Emiliano T. Hudtohan (International Journal of Management and Education in Human Development, 2023)
Geil Browning’s Theory of Emergenetics says that we are a product of nature (DNA) and nurture (influence of school, society, government, business and beliefs). In more vivid details, the Agency Theory of Priestly, Biesta and Robinson enumerates three key dimensions of being an agent who effectively interacts with his/her environment. These are the Performance-Evaluative, 2. Iterative and 3. Projective dimensions. This paper presents the concept of Antifragility of Nassim Taleb as the peak performance of an Agent. The Filipino teacher is presented as an Agent who is Antifragile. The narrative presents a historical reflection on the Filipino teacher as a babaylan, a Christian teacher influenced by a Spanish cultural tradition and a humanist teacher with an American democratic perspective. The paper concludes that: 1. The New Normal is challenging educators to address the creativity and innovation, global and local citizenship, digital technology and interpersonal and intrapersonal relationship inside and outside the classroom. 2. Technology is a key driver of learning and all human endeavors, especially in the age of global civilization, digital civilization, ecological civilization and spiritual civilization. 3. The 21st century Antifragile Teacher Agent must continue to pursue a framework for pedagogy, andragogy, and heutagogy. 4. An Antifragile Teacher Agent must continue explore and upgrade her/his consciousness in the realm of physical, metaphysical and spiritual realities.